Información de los conocimientos actuales que existen sobre sistemas de alimentación de aves y cerdos en las zonas tropicales de América Latina - Buitrago, J.A.; Gómez G., Guillermo G. (International Center for Tropical Agriculture, 1977)
This report includes data on poultry and swine populations and production for L.A. countries. Possibilities of increasing production, especially swine, is more feasible through the improvement of production efficiency than increasing the animal population. Feed availability is the most important limitation in poultry and swine development programs. The poultry industry, due to its better production efficiency and technology, has 1st priority in the use of the conventional feedstuffs available in production areas; whereas swine exploitation depends on the availability of agro-industrial by-products or agricultural residues. In tropical regions there are, however, many underutilized resources that can be used for feeding animals. Data on research of unconventional energetic (e.g., cassava) and protein sources with future potential in nutrition in general and particularly for swine are included. (AS-CIAT)